Bat flies (Diptera, Streblidae and Nycteribiidae) in a Cerrado area of Goiás State, Brazil Dípteros ectoparasitos de morcegos em uma área de cerrado no estado de Goiás, Brasil - Gustavo Graciolli; Marlon Zortéa; Luiz Felipe Alves da Cunha Carvalho (Revista Brasileira de Entomologia, 2010)
A survey of bat flies was carried out in the Brazilian savanna (Cerrado) in the Goiás state, Brazil. We collected 227 specimens of seventeen species belonging to nine genera of Streblidae and seven specimens of four species of Basilia Miranda-Ribeiro, 1903 (Nycteribiidae). Except for Paratrichobius longicrus (Miranda-Ribeiro, 1907) (Streblidae), all species are new recorded in Goiás. Realizamos um levantamento dos ectoparasitas em uma taxocenose de morcegos em uma área de Cerrado no Brasil central, em Goiás. Nós coletamos 227 espécimes de 17 táxons de nove gêneros de Streblidae e sete indivíduos de quatro espécies de Basilia (Nycteribiidae). Excetuando-se Paratrichobius longicrus (Miranda-Ribeiro, 1907) (Streblidae), todas demais espécies são novos registros para o estado de Goiás.